Calcium indium sulfide / palygorskite composite photocatalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202410899332.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-05
AI Technical Summary
[0024]有益效果:本发明与现有技术相比,取得如下显著效果:本发明的硫化铟钙/坡缕石复合材料比表面积大,具有更多的催化活性位点,有效地提高了可见光响应能力,促进了光生电子和空穴的分离,增强了单一硫化铟钙光催化剂的性能,对光催化还原六价铬效果优异。光照60min后,对K2Cr2O7的去除率为98%,还原速率为0.06993min-1。本发明以天然坡缕石、无水氯化钙、四水合氯化铟和硫代乙酰胺为原料,在水和分散剂的作用下,通过水浴加热使硫化铟钙纳米片与坡缕石复合构建异质结,促进了硫化铟钙纳米片的分散,抑制了光生载流子的复合,增强了光催化还原六价铬的效果。
Smart Images

Figure CN118847151B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalyst technology, specifically relating to a photocatalyst, its preparation method and application, and particularly to an indium calcium sulfide / palmitite composite photocatalyst, its preparation method and application. Background Technology
[0002] Hexavalent chromium is a highly toxic and carcinogenic heavy metal ion that is difficult to degrade naturally and can cause chronic poisoning if it enters the human body. In contrast, trivalent chromium has very low toxicity and is an essential trace element for the human body. Against this backdrop, various methods and technologies for removing hexavalent chromium from wastewater have been developed. Photocatalysis can reduce hexavalent chromium to trivalent chromium. Photocatalysis technology is simple to operate, safe, and efficient, and has broad application prospects in energy conversion, environmental remediation, and wastewater treatment.
[0003] Indium calcium sulfide (CaIn2S4) is an indirect bandgap semiconductor material with good response to visible light and strong photocatalytic reduction ability, which is expected to be used for photocatalytic reduction of heavy metal ions.
[0004] However, the photogenerated carriers of unmodified CaIn2S4 are easily recombinated, and the separation of its photogenerated carriers can be effectively improved by constructing composite materials with other materials.
[0005] Pallasites are a good catalyst support, possessing good chemical stability and a large specific surface area.
[0006] This invention constructs a heterojunction by combining CaIn2S4 with palygorskite in order to improve the photocatalytic reduction activity of hexavalent chromium by CaIn2S4 under visible light. Summary of the Invention
[0007] The purpose of this invention is to provide an indium calcium sulfide / palmitite composite photocatalyst that can suppress the recombination of photogenerated carriers in indium calcium sulfide and enhance the photocatalytic effect.
[0008] The second objective of this invention is to provide a method for preparing the above-mentioned indium calcium sulfide / palmitite composite photocatalyst.
[0009] A third objective of this invention is to provide the application of the aforementioned indium calcium sulfide / palmitite composite photocatalyst.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] An indium calcium sulfide / pachymanite composite photocatalyst is formed by combining indium calcium sulfide and palygorskite to form a heterojunction, wherein the mass of palygorskite is 2.5-10% of the mass of indium calcium sulfide.
[0012] Preferably, the mass of palygorskite is 5-10% of the mass of indium calcium sulfide, and most preferably 5%.
[0013] The above-mentioned method for preparing indium calcium sulfide / paspalum composite photocatalyst involves ultrasonically dispersing pspalum in water, with or without the addition of a dispersant, then adding calcium salt, indium salt, and sulfiding agent, mixing them evenly, and then heating the mixture in a water bath under stirring. After the reaction is complete, the product is centrifuged, washed, and dried to obtain the final product.
[0014] The mass-to-volume ratio of palygorskite to water is 1g:800-3200mL, preferably 1g:1600mL.
[0015] The ultrasound described herein has an ultrasound power of 80-120W and an ultrasound dispersion time of 20-40 minutes. Preferably, the ultrasound power is 100W and the ultrasound dispersion time is 30 minutes.
[0016] The palygorskite is added at 2.5-10% of the theoretical yield of indium calcium sulfide to ensure sufficient contact between indium calcium sulfide and palygorskite. Preferably, the palygorskite is added at 5-10% of the theoretical yield of indium calcium sulfide, and most preferably at 5%.
[0017] The dispersant is glycerol; the volume ratio of the dispersant to water is 0-2:4; the preferred method of adding a dispersant is to ensure the catalytic activity of the generated indium calcium sulfide / palmitite composite catalyst, and the preferred volume ratio of the dispersant to water is 1-2:4.
[0018] Wherein, the calcium salt is anhydrous calcium chloride or calcium sulfate; the indium salt is indium chloride tetrahydrate or indium nitrate hydrate; the sulfiding agent is thioacetamide; the molar ratio of the calcium salt, indium salt and sulfiding agent is 1:2:4-8 to ensure that the calcium source and indium source react fully to generate indium calcium sulfide; preferably 1:2:6.
[0019] The water bath heating temperature is 60-100℃, preferably 60-80℃; the reaction time is 1-4h, preferably 2h; the raw materials are fully reacted through water bath heating to form indium calcium sulfide nanosheets.
[0020] This invention does not have a particular limitation on the stirring speed, as long as the reactants are in full and uniform contact.
[0021] The application of the above-mentioned indium calcium sulfide / palmitite composite photocatalyst in the photocatalytic reduction of hexavalent chromium is also within the scope of protection of this invention.
[0022] The specific application method is that the mass ratio of photocatalyst to K2Cr2O7 is 2-20:1, and the visible light intensity is 40-60 mW / cm². 2The visible light irradiation time is 50-80 minutes, reducing hexavalent chromium to trivalent chromium. Preferably, the mass ratio of photocatalyst to K₂Cr₂O₇ is 10:1, and the visible light intensity is 45 mW / cm². 2 Visible light irradiation time is 60 minutes, which reduces hexavalent chromium to trivalent chromium.
[0023] Invention Principle: The indium calcium sulfide / papyrrolidone composite photocatalyst involves in-situ growth of indium calcium sulfide nanosheets on the surface of palyrrolidone nanorods, promoting better dispersion of the indium calcium sulfide nanosheets and effectively inhibiting the recombination of photogenerated charge carriers in indium calcium sulfide. Photogenerated electrons can directly reduce hexavalent chromium to trivalent chromium, or they can first react with oxygen to generate superoxide radicals, which then further react with hexavalent chromium to generate trivalent chromium.
[0024] Beneficial Effects: Compared with existing technologies, this invention achieves the following significant effects: The indium calcium sulfide / palmitite composite material of this invention has a large specific surface area and more catalytic active sites, effectively improving visible light response, promoting the separation of photogenerated electrons and holes, enhancing the performance of single indium calcium sulfide photocatalysts, and exhibiting excellent photocatalytic reduction of hexavalent chromium. After 60 minutes of irradiation, the removal rate of K2Cr2O7 is 98%, and the reduction rate is 0.06993 min. -1 This invention uses natural palygorskite, anhydrous calcium chloride, indium chloride tetrahydrate, and thioacetamide as raw materials. Under the action of water and a dispersant, indium calcium sulfide nanosheets are combined with palygorskite to form a heterostructure through water bath heating. This promotes the dispersion of indium calcium sulfide nanosheets, inhibits the recombination of photogenerated carriers, and enhances the photocatalytic reduction of hexavalent chromium. Attached Figure Description
[0025] Figure 1 These are scanning electron microscope images of the indium calcium sulfide (CaIn2S4) prepared in Example 3, the palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalyst prepared in Example 1.
[0026] Figure 2 The images show the X-ray diffraction spectra of the indium calcium sulfide (CaIn2S4) prepared in Example 3, the palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 4, and 5.
[0027] Figure 3 The Fourier transform infrared spectra are those of the indium calcium sulfide (CaIn2S4) prepared in Example 3, the palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 4, and 5.
[0028] Figure 4 The images show the UV-Vis diffuse reflectance spectra of the indium calcium sulfide (CaIn2S4) prepared in Example 3, the palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 4, and 5.
[0029] Figure 5 These are the photoluminescence spectra of the indium calcium sulfide (CaIn2S4) prepared in Example 3, the palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalyst prepared in Example 1.
[0030] Figure 6 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide (CaIn2S4) prepared in Example 3, palygorskite (Pal) prepared in Example 2, and the indium calcium sulfide / palygorskite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 4, and 5.
[0031] Figure 7 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide / palmite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 1, and 2.
[0032] Figure 8 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide / palmite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 3, and 4.
[0033] Figure 9 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide / palmite (CaIn2S4 / Pal) composite photocatalysts prepared in Examples 1, 5, and 6.
[0034] Figure 10 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide / palmite (CaIn2S4 / Pal) composite photocatalysts prepared in Example 1 and Comparative Example 7.
[0035] Figure 11 The images show the photocatalytic reduction curves and kinetic curves of potassium dichromate by the indium calcium sulfide / palmite (CaIn2S4 / Pal) composite photocatalysts prepared in Example 1 and Comparative Example 8. Detailed Implementation
[0036] The present invention will now be described in further detail.
[0037] Example 1
[0038] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0039] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 6 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 98%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 6 As shown, the reduction rate is 0.06993 min. -1 .
[0040] Example 2
[0041] Add 32 mL of deionized water to a three-necked flask, add 0.2 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0 g of anhydrous calcium chloride, 0 g of indium trichloride tetrahydrate, and 0 g of thioacetamide, and stir for 30 min. Continue stirring and heating in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the treated Pal.
[0042] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 6 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 2%. The reduction curve of K₂Cr₂O₇ followed first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 6 As shown, the reduction rate is 3.90752 × 10⁻⁶. -4 min -1 .
[0043] Example 3
[0044] Add 32 mL of deionized water to a three-necked flask, add 0 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 product.
[0045] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 6 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 72%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 6As shown, the reduction rate is 0.02352 min. -1 .
[0046] Example 4
[0047] Add 32 mL of deionized water to a three-necked flask, add 0.01 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Continue stirring and heating in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 2.5% Pal product.
[0048] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 2.5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and allowed to proceed with a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 6 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 89%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 6 As shown, the reduction rate is 0.03715 min. -1 .
[0049] Example 5
[0050] Add 32 mL of deionized water to a three-necked flask, add 0.04 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 10% Pal product.
[0051] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 10% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 6 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 97%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 6 As shown, the reduction rate is 0.05488 min. -1 .
[0052] Comparative Example 1: The effect of different water bath times.
[0053] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 1 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0054] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 7 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 96.5%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 7 As shown, the reduction rate is 0.06714 min. -1 .
[0055] Comparative Example 2: The effect of different water bath times.
[0056] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 4 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0057] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 7 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 98%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 7 As shown, the reduction rate is 0.05786 min. -1 .
[0058] Comparative Example 3: Effect of different amounts of dispersant added.
[0059] Add 16 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0060] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 8 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 94%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 8 As shown, the reduction rate is 0.04473 min. -1 .
[0061] Comparative Example 4: The effect of not adding dispersant.
[0062] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 0 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0063] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 8 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 97%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 8 As shown, the reduction rate is 0.05866 min. -1 .
[0064] Comparative Example 5: The effect of different water bath temperatures.
[0065] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in a 60 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0066] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 9 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 97%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 9 As shown, the reduction rate is 0.06092 min. -1 .
[0067] Comparative Example 6: The effect of different water bath temperatures.
[0068] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in a 100 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0069] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 9 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 97%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 9 As shown, the reduction rate is 0.05658 min. -1 .
[0070] Comparative Example 7: Effect of different ratios of calcium salt, indium salt and sulfiding agent.
[0071] Add 32 mL of deionized water to a three-necked flask, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g (1 mmol) of anhydrous calcium chloride, 0.5865 g (2 mmol) of indium trichloride tetrahydrate, and 0.6011 g (8 mmol) of thioacetamide, and stir for 30 min. Heat and stir continuously in an 80 °C water bath for 2 h. After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0072] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 10As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 97%. The reduction curve of K₂Cr₂O₇ conformed to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 10 As shown, the reduction rate is 0.06235 min. -1 .
[0073] Comparative Example 8: The effect of different preparation methods.
[0074] Add 32 mL of deionized water to a 100 mL beaker, add 0.02 g of palygorskite (Pal), and sonicate at 100 W for 30 min. Add 8 mL of glycerol and stir for 30 min. Add 0.111 g of anhydrous calcium chloride (1 mmol), 0.5865 g of indium trichloride tetrahydrate (2 mmol), and 0.4508 g (6 mmol) of thioacetamide, and stir for 30 min. Transfer the prepared solution to the inner liner of a 100 mL polytetrafluoroethylene reactor and hydrothermally react at 80 °C for 2 h (without stirring). After cooling to room temperature, wash three times with ethanol and dry under vacuum at 60 °C for 12 h to obtain the CaIn2S4 / 5%Pal product.
[0075] 1 mL of 2 g / L K₂Cr₂O₇ mother liquor was added to a photocatalytic reaction flask, and water was added to 50 mL to obtain a 40 mg / L K₂Cr₂O₇ solution. 4 mL of this solution was used as a reference solution. 20 mg of CaIn₂S₄ / 5% Pal catalyst was weighed and added to the reactor, stirred thoroughly, and subjected to a 30-minute dark chamber reaction. After the dark reaction was complete, a xenon lamp was turned on, and the reaction system was irradiated with visible light. Samples were taken every 10 minutes, and the mixture was centrifuged to separate the supernatant. The ultraviolet-visible absorption spectra of the K₂Cr₂O₇ solution under different irradiation times were measured using a UV-Vis spectrophotometer. The absorbance at the maximum absorption wavelength of 258 nm was selected to obtain the K₂Cr₂O₇ solution concentration versus time curve. The results are as follows: Figure 11 As shown, after 60 minutes of illumination, the removal rate of K₂Cr₂O₇ was 77%. The reduction curve of K₂Cr₂O₇ conforms to first-order kinetics, and the fitted kinetic curve is shown in the figure. Figure 11 As shown, the reduction rate is 0.02549 min. -1 .
[0076] As can be seen from the examples and comparative examples, the combination of indium calcium sulfide and palygorskite improves the removal efficiency of hexavalent chromium. Specifically, when the molar ratio of calcium salt, indium salt, and sulfiding agent is 1:2:6, the mass ratio of indium calcium sulfide to palygorskite is 5%, and the ratio of glycerol to water in the reaction solvent is 1:4, the CaIn2S4 / 5%Pal solution prepared by reacting at 80°C for 2 hours using the water bath method achieves the highest efficiency in removing hexavalent chromium. After 60 minutes of illumination, the removal rate of K2Cr2O7 is 98%. The reduction rate of K2Cr2O7 is 0.06993 min. -1 It is 2.97 times the photocatalytic reduction rate of K2Cr2O7 by pure CaIn2S4.
[0077] This invention provides an indium calcium sulfide / papyrrolidone composite photocatalyst, its preparation method, and its application. Many methods and approaches exist for implementing this technical solution; the above description is merely a preferred embodiment of the invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications should also be considered within the scope of protection of this invention. All components not explicitly stated in this embodiment can be implemented using existing technologies.
Claims
1. Application of an indium calcium sulfide / paspalum composite photocatalyst in the photocatalytic reduction of hexavalent chromium. in, The aforementioned indium calcium sulfide / pachymanite composite photocatalyst is formed by combining indium calcium sulfide and palygorskite to form a heterojunction, wherein the mass of palygorskite is 5-10% of the mass of indium calcium sulfide; The indium calcium sulfide / palmitite composite photocatalyst was prepared by the following method: palmitite was ultrasonically dispersed in water, a dispersant was added, and then calcium salt, indium salt and sulfide agent were added. After mixing evenly, the mixture was heated in a water bath under stirring. After the reaction was completed, the product was centrifuged, washed and dried to obtain the final product. The dispersant is glycerol; The volume ratio of the dispersant to water is 1:4; The water bath heating temperature is 60-100 ℃, and the reaction time is 1-4 h.
2. The application according to claim 1, characterized in that, The mass-to-volume ratio of palygorskite to water is 1g:800-3200mL.
3. The application according to claim 1, characterized in that, The ultrasound described herein has an ultrasound power of 80-120W and an ultrasound dispersion time of 20-40 minutes.
4. The application according to claim 1, characterized in that, The calcium salt is anhydrous calcium chloride or calcium sulfate; the indium salt is indium chloride tetrahydrate or indium nitrate hydrate; the sulfiding agent is thioacetamide; and the molar ratio of the calcium salt, indium salt and sulfiding agent is 1:2:4-8.
5. The application according to claim 1, characterized in that, The mass ratio of photocatalyst to K2Cr2O7 is 2-20:1, and the visible light intensity is 40-60 mW / cm. 2 When exposed to visible light for 50-80 minutes, hexavalent chromium is reduced to trivalent chromium.
Citation Information
Patent Citations
Ultrathin CaIn2S4 nanosheet photocatalytic material and preparation method thereof
CN113751026A
Indium zinc sulfide / attapulgite composite photocatalyst as well as preparation method and application thereof
CN118045607A